Analisis Wacana Kritis Media Online Detik.Com Berita Pengadaan Seragam LV Dewan Perwakilan Rakyat Kota Tangerang - Khotimah, Khusnul; Hidayat, Ryan (Deiksis, 2023)
This study's problem formulation is based on van Dijk's critical discourse, which includes text, social cognition, and social environment. The descriptive qualitative research method was used in this study. In August 2021, the internet media "detik.com" was used as the data source for this investigation. The news "Procurement of official clothes for the Tangerang City DPRD brand LV" was the focus of this investigation, which included of 5 articles. The following is the conclusion: According to detik.com, the structure of the news text on the procurement of LV brand official clothes portrays the Tangerang City DPRD as the initiator of the procurement of LV brand official clothes in a negative light, while positively portraying the auction winner. The sort of knowledge used in the news, namely personal, institutional, and organizational knowledge, reveals the social cognition included therein. The social situation mentioned in the detik.com news story represents a societal social ideal that prioritizes the public good over personal gain. The purchase of official clothing is a personal interest that can be set aside if there is a more pressing public concern that needs to be addressed first. The cancellation of official clothes procurement with the LV brand, which has a spectacular price, reflects societal standards in Indonesian organizations.